(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The new trade policy of India is looking towards East-Asian countries since its implementation of New Economic Reforms by 1990-1991. Sporadic and haphazard liberalization steps had been taken up in the later half of the eighties, but these were ineffective on the whole. The Gulf war in 1990 sharply accentuated many economic problems in India. In addition, political instability was prevailing in that period. These developments led to an erosion of international confidence in India. Now, the governments had two major goals: (a) restoration of economic stability by cutting down the fiscal deficits and bringing stability in the Balance of Payments and (b) to make structural changes or adjustments in the economy; a process of reforms which had been going on for the last decades but on an insignificant pace, but now to be taken up on a wider scale and at a pace whose impact would be direct and seen in the long term. There is now general agreement that the process of economic reforms must be strengthened and deepened. Whereas there was a well-developed consensus among economists about the first order problem which then afflicted the Indian economic policy, the same is not true for second generation reforms.